Pemberdayaan Masyarakat Melalui Penyuluhan Perawatan Gigi Dan Mulut Pada Anak Sekolah TK Kabar Baik di Desa Ajibaho Kabupaten Deli Serdang Tahun 2022 - Arva Rochmawati; Desi Anggraini (Journal of Community Development, 2022)
Cavities are still a common complaint in both children and adults. This condition cannot be ignored as it can affect a person's quality of life by causing pain, discomfort, disability, acute and chronic infections, eating and sleeping disorders, as well as a high risk of hospitalization. As a result, medical costs can increase significantly. One of the main causes of oral health problems in children is the lack of knowledge about how to maintain oral health. To address this issue, a health counseling was conducted focusing on "Dental and Oral Care in School Children of Kabar Baik Kindergarten in Ajibaho Village, Biru-biru District, Deli Serdang Regency." This counseling involved 32 students from Kabar Baik Kindergarten. Through this activity, the students were introduced to the importance of oral care, as well as practical ways to maintain dental hygiene. The counseling included learning about proper brushing techniques, the importance of a healthy diet, and prevention of excessive sugar consumption. In addition, students were also given information on good habits to maintain dental health, such as avoiding nail biting or finger sucking. By involving children from an early age in education about oral care, it is hoped that their awareness of the importance of maintaining oral health will increase. This counseling aims to prevent cavities in the future and improve children's quality of life with healthy habits implemented early on.